Experimental Study of PGC-01 Grounding Cable Addition on Urate Evo-7 Engine Wiring System by Pandawa Team - Ahmad Khusom Kurniawan; Samsudin Anis; Muhammad Bagus Laroybafih; Yasiru Pisawalus Samak; Dziki Early Al Husni; Ilham Ariosepto Nugroho (Journal of Creativity Student, 2026)
The ever-increasing demand for fossil fuels and the environmental impact of electric vehicles have driven innovation in Internal Combustion Engine (ICE) efficiency. This study explores the effect of installing a silver-based PGC-01 grounding cable on the engine wiring system of the Urate Evo-7 Pandawa Team energy-efficient vehicle. This study employed an experimental method with three different installation schemes. Scheme 1 connects the battery to the negative ignition coil and the throttle body sensor. Scheme 2 connects the battery to the negative ignition coil and the crankcase. Scheme 3 connects the battery to the negative ignition coil and the negative spark plug. Testing was conducted statically at 3000 rpm and dynamically with acceleration variations of 0–30 km/h, 0–35 km/h, and 0–40 km/h. The results show that Scheme 3 has the greatest impact on reducing fuel consumption. The reduction reached 12.1% in the static test and 16% in the dynamic acceleration test from 0 to 35 km/h. This makes it the most optimal configuration for the “kill and run” strategy in energy-efficient vehicle competitions.